BREEDERS' LEVEL OF KNOWLEDGE IN DETECTION OF OESTRUS TO SUPPORT THE SUCCESS OF ARTIFICIAL INSEMINATION (AI) ON CATTLE IN TUBBI TARAMANU DISTRICT, POLEWALI MANDAR - Susanti S, Irma; Erfiana, Dwi; Agustina, Agustina; Nuraliah, Siti; Hikmawaty, Hikmawaty; Dahniar, Dahniar; Utami, Rahmawati Ning; Sukoco, Hendro (Agros Journal of Agriculture Science, 2024)
Artificial insemination (AI) is one of the biotechnologies in the field of livestock reproduction that allows humans to mate female livestock without the need for a male, the purpose of this study was to determine the extent of knowledge of breeders on the symptoms of oestrus in cattle to the linkage of artificial insemination (AI). The purpose of this study was to determine the extent of knowledge of farmers on the symptoms of lambing in cattle to the linkage of artificial insemination (AI). this research was conducted in the form of a field survey, while data collection was carried out by interview. In this study, the analysis technique used was descriptive analysis. Based on the results of the study, it was found that the level of knowledge of farmers on the detection of oestrus in livestock to support the success of IB in cattle is out of 100 respondents who know 2.47%, know enough 0.53%, and do not know 4.71%. This value is influenced by several factors, one of which is age, the higher the age of the breeder, the more difficult it is to accept new technology, namely AI, because the breeder already feels comfortable with the knowledge they get from generation to generation. Keywords:. Artificial insemination, Knowledge, Oestrus, Cattle